2003
DOI: 10.1046/j.0004-8666.2003.00001.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐obstetric surgery during gestation: Risk factors for lower birthweight

Abstract: While non-obstetric surgery appears to be relatively safe during gestation, general anaesthesia, longer surgery time, and intra-abdominal procedures are associated with lower birthweights.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
3
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 16 publications
5
45
3
1
Order By: Relevance
“…There were no significant differences in the birthweight between the two groups. Moreover, Jenkins et al 43 reported that general anaesthesia, longer surgery duration and intra-abdominal procedures are associated with lower birthweight.…”
Section: Stillbirth and Low Birthweightmentioning
confidence: 99%
“…There were no significant differences in the birthweight between the two groups. Moreover, Jenkins et al 43 reported that general anaesthesia, longer surgery duration and intra-abdominal procedures are associated with lower birthweight.…”
Section: Stillbirth and Low Birthweightmentioning
confidence: 99%
“…Jenkins et al found that surgery in the second trimester results in the lowest rate of preterm birth compared to the first trimester. 5 In another study, the rate of major birth defects among women who underwent non-obstetric surgery in the first trimester was reported as 3.9%. 4 A decrease in maternal blood flow may cause reduced placental perfusion and fetal hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…malities, spontaneous abortion and lower birth weight. 4,5 We reported the case of a patient with 8 weeks of pregnancy who underwent successful fracture surgery under combined spinal-epidural anaesthesia.…”
Section: Anesthetic Management For Lower Extremity Fractures Surgery mentioning
confidence: 99%
“…In the late second trimester surgery should be delayed to at least 28 weeks, when the fetal survival of over 90% is achievable (Loughlin, KR., 1995). In the early second trimester however, immediate surgery is recommended by some of the authors due to the low risk of the fetal loss (FazeliMatin, S., et al, 1998;Gnessin, E., et al, 2002;Jenkins, TM., et al, 2003).…”
Section: Discussionmentioning
confidence: 99%